(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Generally reputed to be Sir Sayyed, was an Indianinstructor and lawmaker, and an Islamic reformer and pioneer. Sir Sayyed pioneered cutting edge instructionfor the Muslim neighborhood in Indiaby establishing the Muhammedan Anglo-Oriental College, which later improvedinto the Aligarh Muslim University.His work gave ascent to another era of Muslim learned people and legislatorswho created the Aligarh development to securethe political fate of Muslims in India.